Pronoun use in preclinical and early stages of Alzheimer's dementia - Bittner, Dagmar; Frankenberg, Claudia; Schröder, Johannes (Computer speech and language, 2024)
The present study aims at improving the predictive power of the use of pronouns in computational modeling of the risk of Alzheimer's dementia (AD) by (i) further determining the onset of increased pronoun use in AD and (ii) providing insights into the linguistic contexts affected by the increase early on. Pronoun use was compared longitudinally between subjects who either stayed cognitively intact (CTR-group, n = 5) or who had developed AD upon follow-up after 10-12 years (AD-group, n = 5). Data were taken from semi-structured biographical interviews, which stem from the Interdisciplinary Longitudinal Study on Adult Development and Aging (ILSE). The first interview (baseline) was conducted when all participants were still cognitively healthy. Analyses concerned the proportional distribution of 12 pronoun types and linguistic contexts of increased use. Already at baseline, the AD-group produced a significantly higher proportion of D-pronouns (der, die, das, etc.) than the CTR-group. The increase in D-pronouns did not affect linguistic contexts favoring the use of personal pronouns. Instead, we found a significantly higher proportion of D-pronouns referring to family members and a significantly higher proportion of personal pronouns referring to non-family humans in the AD-group than in the CTR-group. Our results suggest that the predictive power of the use of pronouns can be significantly improved in computational modeling of the risk of AD by assessing language material that induces the use of pronouns in linguistic contexts affected by the increase.